The Pengaruh Pengaruh Kualitas Pelayanan Petugas Pajak, Sanksi Perpajakan, Tarif Pajak Dan Kondisi Keuangan Terhadap Kepatuhan Wajib Umkm Selama Masa Pandemi Covid-19 - Rifka Ayu Irawan; Anisa Putri (JRAK: Journal of Accounting Research and Computerized Accounting, 2022)
This study aims to determine the effect of tax officer service quality, tax sanctions, tax rates and financial conditions on MSME taxpayer compliance during the COVID-19 pandemic. The research method uses quantitative methods. The study was conducted on MSMEs in Bekasi City with a population of 23,000 in 2021. The research sample used was 100 respondents from MSME entrepreneurs in Bekasi City. With a sampling technique using purposive sampling. The regression analysis method used is multiple linear regression. The results of statistical tests, variable service quality of tax officers, tax sanctions and financial conditions have a positive and significant effect on MSME taxpayer compliance in Bekasi City. While the tax rate has no effect on the compliance of MSME taxpayers in Bekasi City.